2018
DOI: 10.1016/j.eurpolymj.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Melt stabilization of PE with natural antioxidants: Comparison of rutin and quercetin

Abstract: The stabilization effect of a flavonoid type natural antioxidant, rutin, was compared to that of quercetin in polyethylene. Additive concentrations changed between 0 and 500 ppm in several steps and also 1000 ppm Sandostab PEPQ phosphorus secondary stabilizer was added to each compound. Stabilization efficiency was determined by changes in vinyl group content, melt flow rate, oxygen induction time, color and the consumption of the secondary antioxidant during multiple extrusions. The results showed that rutin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…The major active compounds in PCE are caftaric acid, polydatin, rutin, quercitrin, and resveratrol. The five active compounds are present in many natural plant extracts, and previous studies have demonstrated that they have anti-inflammatory and anti-oxidative properties [ 48 , 49 , 50 ]. Therefore, PCE may promote anti-oxidative activity in DED by recovering expression of anti-oxidant proteins such as HO-1, SOD-1, and GPx in hyperosmolar stressed HCECs.…”
Section: Discussionmentioning
confidence: 99%
“…The major active compounds in PCE are caftaric acid, polydatin, rutin, quercitrin, and resveratrol. The five active compounds are present in many natural plant extracts, and previous studies have demonstrated that they have anti-inflammatory and anti-oxidative properties [ 48 , 49 , 50 ]. Therefore, PCE may promote anti-oxidative activity in DED by recovering expression of anti-oxidant proteins such as HO-1, SOD-1, and GPx in hyperosmolar stressed HCECs.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine was loaded in the hydrogels by soaking procedure with a loading efficiency >85% for both hydrogels and a loading percent, DL(%), of 8.0 and 8.5 for HB and HQ, respectively. The slight difference in the DL values can be related to the ability of Q moieties to interact with drug molecules via aromatic interactions, resulting in higher affinity of caffeine toward HQ.…”
Section: Resultsmentioning
confidence: 99%
“…A series of research results suggested that the effects of natural antioxidants in stabilizing of polyolefin come from the interaction of natural antioxidant and secondary antioxidant. [12,15,16,18] Thus, the interaction between puerarin and PEPQ was discussed in this section. For comparison, PE or PP modified with only PEPQ (PE-P 0 -P and PP-P 0 -P samlpes) and PE or PP modified with only puerarin (PE-P 1200 and PP-P 1200 samlpes) were prepared.…”
Section: Interaction Of Puerarin and Pepqmentioning
confidence: 99%
“…Quite a few of natural compounds derived from plants have been used as stabilizer for foods [3][4]5,6] and polymer. [7][8][9][10][11][12][13][14][15][16][17][18][19] Lignin that comes from cell walls of woods and grasses is a natural macromolecule polyphenol. PE mixed with a mass of lignin exhibited preferable thermooxidative stability and processing stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation